Mesa redonda sobre "L’université sans condition" de J. Derrida - Blesa, Túa; Ferrero Carracedo, Luis; De Peretti, Cristina; Vázquez, Manuel E.; Rampérez, Fernando (Escritura e Imagen, 2012)
Mesa redonda sobre L’université sans condition de J. Derrida